As 'synapses' become 'protoplasmic kisses': Symmetry across clinical reasoning and poetry. Issue 3 (13th November 2022) - Bleakley, Alan; Neilson, Shane
Abstract: Context: We argue that biomedicine at root is not primarily instrumental, but shares aesthetic, ethical and political values with poetry. Yet an instrumentalist bias in medical pedagogy can lead to frustration of biomedicine's potential. Such unfulfilled potential is exposed when making a comparison with poetry, a knowledge system that expressly engages a range of value systems. How then to recover biomedical language's riches for medical education's gain? Methods: We combine scientific and artistic approaches by positing a common frame to which both medicine and poetry can aspire: the 'high‐water mark' of language. Poetry's language is complex, intensive and connotative—concerned with mood, ambiguity, metaphor and embodiment. Biomedicine potentially engages with such linguistic complexities, particularly in metaphor production, yet persistently falls away from this high‐water mark of language, reducing connotative language to denotation or literal meanings. We describe such instances of frustrated potential as 'trying to accelerate with the brake on'. This paradoxical state has become habitual in medical education. The resultant lack of productive metaphor insulates pedagogy from mood, separating it from the vernacular as a specialist tongue that ensures identification with the medical community of practice. Such language can alienate both patients and poets for the same reason: it is less human than technical. Conclusions: Using the example of clinical reasoning and attendant diagnostic work, we show that reductions from the connotative to the denotative not only mask but also contradict the complexity of implicit, embedded and distributed cognitive structures, creating a tension that medical education consistently fails to either resolve or draw upon as a resource. Further, poetry too has a complex set of implicit rules and formative structures that shape composition. These structures show symmetry, correspondence or even isomorphism with medical cognition, where both can aspire to activity that is aesthetically rich, intense and cognitively elegant. Abstract : The authors argue that the reductive and instrumental use of language common to biomedical science flattens expressiveness and can alienate patients by showing how rich language can result in better clinical judgement.